Acute Zonal Occult Outer Retinopathy: Vision Loss in an Active Duty Soldier - Courtney M. Crawford; Bruce A. Rivers; Mark Nelson (Case Reports in Medicine)
Objective. To describe a case of acute zonal occult outer retinopathy (AZOOR) in an active duty patient. Methods. In this paper we studied fundus photographs, optical coherence tomograph, Humphrey visual field 30-2, fundus autofluorescence images, fluorescein angiograms, and electroretinography. Results. Exam findings on presentation: a 34-year-old American Indian female presented with bilateral photopsias, early RPE irregularity, and an early temporal visual field defect. Progression RPE damage and visual field defect along with ERG findings support final diagnosis of AZOOR. Conclusion. AZOOR may initially be identified as a broader category of disease called the “AZOOR complex of disorders”. Specific visual field defects, ERG results, and clinical exam findings will help distinguish AZOOR from other similar disorders.